Fractionation and long-term laboratory incubation to measure soil organic matter dynamics - Paul, Eldor A., author; Wright, S., author; Collins, H. P., author; Haile-Mariam, S., author; Soil Science Society of America, publisher (Colorado State University. Libraries, 2008)
Soil organic matter (SOM) in agricultural soils comprises a significant part of the global terrestrial C pool. It has often been characterized by utilizing a combination of chemical dispersion of the soil followed by physical separation. We fractionated soil samples under continuous corn (Zea mays L.) rotations at four long-term sites in the Corn Belt to determine the concentration of C and N associated with soil fractions (light fraction [LF], particulate organic matter [POM], silt size, clay size, and Bradford reactive soil protein [BRSP]) and to identify the change in C concentration and δ13C signal of each fraction using laboratory incubations. Light fractions comprised 3 to 5% of the soil organic carbon (SOC), with no significant difference between conventional tillage (CT) and no-till (NT) treatments. The POM fraction accounted for 5 to 11% of the SOC in the soils with >30% clay and 17 to 23% for the soils with <20% clay. The clay-size fraction contained the highest proportion of SOC. Measurement of 13C during long-term incubation showed that the average mean residence time (MRT) of corn-derived C in the LF was 3.5 yr, whereas the POM fractions ranged from 6 to 12 yr. The 13C changes during incubation show that both fractions consist of a mixture of active and resistant materials, with movement between fractions. The BRSP has long MRTs except in the NT Hoytville soil. Measurement of the dyna mics of these fractions provides a basis for C models to test the impacts of land use and management on C sequestration.
Keywords: CO2; soil C; soil N; SOM; global terrestrial C and N pools